2021
DOI: 10.20473/amnt.v5i2.2021.166-172
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutrition Intervention On Snack's Eating Habits and Anthropometric Status of College Students in Malang City

Abstract: Background: Problems that arise in students based on the results of the 2016 study indicate that more than 80% of students like to eat unhealthy snacks such as packaging snacks, fried foods, instant noodles, and meatballs. Where snacks contain high energy, carbohydrates, protein, saturated fat, and salt. The excess energy and nutrients intake are related to increasing the metabolic incidence of syndromes and the main risk factors for cardiovascular disease.Objectives: This study aims to determine the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…14 Previous studies have shown that healthy snacks also correlate as a protective factor among obesity in subjects. 23 To pinpoint the outcomes of this study, it is crucial to analyze the intake of healthy and unhealthy snacks specifically.…”
Section: Resultsmentioning
confidence: 99%
“…14 Previous studies have shown that healthy snacks also correlate as a protective factor among obesity in subjects. 23 To pinpoint the outcomes of this study, it is crucial to analyze the intake of healthy and unhealthy snacks specifically.…”
Section: Resultsmentioning
confidence: 99%